Enough of quadratic equations guys let us try something new

Algebra Level 4

If a x 17 + b x 16 + 1 ax^{17} + bx^{16}+1 is divisible by x 2 x 1 x^{2}-x-1 , Then find the integral value of a a .


The answer is 987.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tapas Mazumdar
May 27, 2017

We have

x 2 x 1 = 0 x = 1 ± 5 2 \begin{aligned} & x^2 - x - 1 =0 \\ \implies & x = \dfrac{1 \pm \sqrt{5}}{2} \end{aligned}

x 2 x 1 = 0 [ x ( 1 + 5 2 ) ] [ x ( 1 5 2 ) ] \therefore \ x^2 -x - 1 = 0 \implies \left[ x - \left( \dfrac{1 + \sqrt{5}}{2} \right) \right] \left[ x - \left( \dfrac{1 - \sqrt{5}}{2} \right) \right]

Let the roots of the above quadratic be denoted by ϕ = 1 + 5 2 \phi = \dfrac{1 + \sqrt{5}}{2} and ψ = 1 5 2 \psi = \dfrac{1 - \sqrt{5}}{2} respectively. Observe that ϕ ψ = ( 1 + 5 2 ) ( 1 5 2 ) = 4 4 = 1 \phi \cdot \psi = \left( \dfrac{1 + \sqrt{5}}{2} \right) \left( \dfrac{1 - \sqrt{5}}{2} \right) = - \dfrac{4}{4} = -1 .

Now since the quadratic is a factor of a x 17 + b x 16 + 1 ax^{17} + bx^{16} + 1 therefore it's roots must also be two of the possible 17 17 roots of a x 17 + b x 16 + 1 ax^{17} + bx^{16} + 1 .

Thus

{ a ϕ 17 + b ϕ 16 + 1 = 0 a ψ 17 + b ψ 16 + 1 = 0 { a ϕ 17 + b ϕ 16 + 1 = 0 a ( 1 ϕ ) 17 + b ( 1 ϕ ) 16 + 1 = 0 { a ϕ 17 + b ϕ 16 + 1 = 0 a + b ϕ + ϕ 17 = 0 { a ϕ 17 + b ϕ 16 + 1 = 0 a ϕ 15 + b ϕ 16 + ϕ 32 = 0 \begin{aligned} & \begin{cases} a\phi^{17} + b\phi^{16} + 1 = 0 \\ a\psi^{17} + b\psi^{16} + 1 = 0 \end{cases} \\ \\ \implies & \begin{cases} a\phi^{17} + b\phi^{16} + 1 = 0 \\ a {\left( - \dfrac 1 \phi \right)}^{17} + b{\left( - \dfrac 1 \phi \right)}^{16} + 1 = 0 \end{cases} \\ \\ \implies & \begin{cases} a\phi^{17} + b\phi^{16} + 1 = 0 \\ - a + b\phi + \phi^{17} = 0 \end{cases} \\ \\ \implies & \begin{cases} {\color{#3D99F6} a\phi^{17} + b\phi^{16} + 1 = 0} \\ {\color{#3D99F6} - a\phi^{15} + b\phi^{16} + \phi^{32} = 0} \end{cases} \end{aligned}

Subtracting the final two equations gives

a ϕ 17 + a ϕ 15 + 1 ϕ 32 = 0 a = ϕ 32 1 ϕ 17 + ϕ 15 = 987 a \phi^{17} + a \phi^{15} + 1 - \phi^{32} = 0 \implies a = \dfrac{\phi^{32} - 1}{\phi^{17} + \phi^{15}} = \boxed{987}

This problem​ is already on brilliant. See this

Rahil Sehgal - 4 years ago

Hey, thanks for solution but I want to know that how did you solved the last expression that one which has power 32. The expression in the last......did you just put the values of phi or what?

Shubham Joshi - 4 years ago

Log in to reply

Yes, that was done by calculator aid only. The better method to solve this problem is given by Brian Charlesworth in the solution of this problem .

Tapas Mazumdar - 4 years ago

Log in to reply

Ok thanks sir! Thank you so much!

Shubham Joshi - 4 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...